Maintaining Christian virtues and ethos in Christian universities in Ghana: The reality, challenges and the way forward - White, Peter (HTS teologiese studies, 2017)
Christian universities are established to integrate Christian faith, principles and virtues into their academic programmes with the expectation that through this holistic Christocentric education, students will be well-prepared to serve and to contribute positively to transform society. Although this approach to education is good, it however does not come without the challenge of how to maintain these Christian virtues in light of increasing secularisation and permissiveness in contemporary society. This article examines the realities and challenges of maintaining Christian virtues and ethos in Christian universities in Ghana and recommends some helpful solutions. The study employed eclectic methodology in data gathering and analyses. The research revealed that for a university to be called a Christian university, it must have at its core the vision for Christ-centredness, mission mindedness and discipleship focus. This must also be reflected in the attitude of both students and staff in the way they relate to and manage God’s resources.